Differences in clinical outcome between docetaxel and abiraterone acetate as the first-line treatment in chemo-naïve metastatic castration-resistant prostate cancer patients with or without the ineligible clinical factors of the COU-AA-302 study - Darren M.C. Poon; Kuen Chan; Siu H. Lee; Tim W. Chan; Henry Sze; Eric K.C. Lee; Daisy Lam; Michelle F.T. Chan (Prostate International, 2018)
Background: This study aimed to compare the efficacy of abiraterone acetate (AA) versus docetaxel (T) as first-line treatment in chemo-naïve metastatic castration-resistant prostate cancer (mCRPC) patients with or without the ineligible factors of the COU-AA-302 study (presence of visceral metastases, symptomatic disease, and/or Eastern Cooperative Oncology Group performance status ≥ 2). Materials and methods: The clinical records of chemo-naïve mCRPC patients who received AA in six public oncology centers or T in two of these centers between 2003 and 2014 were reviewed. The survival time was compared among four subgroups of patients: those with ineligible factors administered AA (Group Ineligible–AA) or T (Group Ineligible–T), and those without ineligible factors and administered AA (Group Eligible–AA) or T (Group Eligible–T). Results: During the study period, we identified 115 mCRPC patients who received AA or T, among whom 29, 36, 29, and 21 patients were classified as Groups Ineligible–AA, Ineligible–T, Eligible–AA, and Eligible–T, respectively. Both Group Ineligible–AA and Group Eligible–AA had significantly longer progression-free survival (PFS) and similar overall survival (OS) as Group Ineligible–T and Group Eligible–T (Ineligible, PFS: 6.3 vs. 5.9 months, P=0.0234, OS: 7.8 vs. 15.7 months, P=0.1601; Eligible, PFS: 9.8 vs. 5.6 months, P=0.0437, OS: 20.5 vs. 18.2 months, P=0.7820). Conclusions: Compared to T, AA treatment resulted in longer PFS and similar OS in chemo-naïve mCRPC patients, irrespective of the presence of ineligible factors, suggesting that the initial treatment by AA may still be beneficial to those with the aforementioned ineligible factors.